2017
DOI: 10.18632/oncotarget.15271
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms rs1800012 in COL1A1 with sports-related tendon and ligament injuries: a meta-analysis

Abstract: It has been reported that the single nucleotide polymorphism (SNP) rs1800012 in COL1A1 might be associated with the susceptibility to sports-related tendon and ligament injuries such as ACL injuries, Achilles tendon injuries, shoulder dislocations and tennis elbow. But the data from different studies have been conflicting. Here we attempted to systematically summarize and clarify the association between the SNP and sports-related tendon and ligament injuries risk. Six eligible studies including 933 cases and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
2
38
0
1
Order By: Relevance
“…: osteogenesis imperfecta) 15,17,21 . Complex gene-gene and gene-environment interactions alter the severity of the phenotype in non-Mendelian pattern inherited conditions like ACL tear 7,21 . Recently, Yao et al linked the rs1107946 polymorphism to the geometric size of ACL in the Chinese population 22 .…”
Section: Muscles Ligaments and Tendonsmentioning
confidence: 99%
See 3 more Smart Citations
“…: osteogenesis imperfecta) 15,17,21 . Complex gene-gene and gene-environment interactions alter the severity of the phenotype in non-Mendelian pattern inherited conditions like ACL tear 7,21 . Recently, Yao et al linked the rs1107946 polymorphism to the geometric size of ACL in the Chinese population 22 .…”
Section: Muscles Ligaments and Tendonsmentioning
confidence: 99%
“…Wang et al examined association of SNPs and sports-related ligament and tendon COL1A1 injuries (like ACL tear, Achilles tendinopathy, tennis elbow and should dislocation). They observed that the rare TT genotype may be protective against these sports-related ligament/tendon injuries 7 . Apart from sports injuries, the rs18000012 SNP of COL1A1 gene has most notably been linked to osteoporosis; various other complex disorders of connective tissue, including, myocardial infarction, lumbar disc disease and stress urinary incontinence have also shown association with this SNP [26][27][28][29] .…”
Section: Muscles Ligaments and Tendonsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between gene polymorphism of COL1A1 gene and osteoporosis is mostly reported [ 3 , 4 ]. Some articles also found the connection between COL1A1 gene and other diseases in musculoskeletal system, such as sports-related tendon and ligament injuries [ 5 ], osteogenesis imperfecta [ 6 , 7 ], osteosarcoma [ 8 ], idiopathic carpal tunnel syndrome [ 9 ]. And among various polymorphisms within the COL1A1 gene, the most frequently studied polymorphism is the +1245G/T polymorphism (rs1800012, Sp1), which is a G to T polymorphism siting within the first intron of COL1A1 gene influencing a binding site for the transcription factor Sp1 [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%